mtDNA, Metastasis, and the Mitochondrial Unfolded Protein Response (UPRmt) - Kenny, Timothy C.; Germain, Doris (Frontiers in Cell and Developmental Biology, 2017)
While several studies have confirmed a link between mitochondrial DNA (mtDNA) mutations and cancer cell metastasis, much debate remains regarding the nature of the alternations in mtDNA leading to this effect. Meanwhile, the mitochondrial unfolded protein response (UPRmt) has gained much attention in recent years, with most studies of this pathway focusing on its role in aging. However, the UPRmt has also been studied in the context of cancer. More recent work suggests that rather than a single mutation or alternation, specific combinatorial mtDNA landscapes able to activate the UPRmt may be those that are selected by metastatic cells, while mtDNA landscapes unable to activate the UPRmt do not. This review aims at offering an overview of the confusing literature on mtDNA mutations and metastasis and the more recent work on the UPRmt in this setting.